THE USE OF AUDIO VISUAL AIDS IN MASTERING ENGLISH VOCABULARIES - ROSDIANA SHADIQIN (English Study Program University of Pasir Pengaraian, 2016)
This article reports the finding of the analysis of use of audio visual aids to enrich students’ English vocabularies mastery at grade X of state senior high school 3 of Tambusai Utara. The aspects explored in the study covered activities done by the students in the learning of English vocabularies.. The research employed the descriptive quantitative design and the instruments used in collecting the data were a set of questionnaire and tests. The data analysis covered the use of product moment. The findings showed that use audio visual aids could better give positive effect to the students’ English vocabularies mastery at grade XI of state seniorhigh school 3 of Tambusai Utara.